2012
DOI: 10.6000/1927-3037/2012.01.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Solution Viscometry Studies on a Therapeutic Mixture of Non-digestible Carbohydrates

Abstract: Abstract:Recent work has shown the beneficial effects of a proprietary mixture of three non-digestible carbohydrates: konjac glucomannan, xanthan and alginate and these effects have been linked with a synergistic interaction observable with analytical ultracentrifugation, rheological and NMR measurements. These observations have been supported by fundamental dilute solution viscosity studies. Preparations of konjac glucomannan, xanthan and alginate have been checked with regards their molecular integrity (mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The carbohydrate properties of PGX have been previously described [12,13,14] and show that an interaction between a konjac glucomannan–xanthan gum complex and sodium alginate forms a new, ternary complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate properties of PGX have been previously described [12,13,14] and show that an interaction between a konjac glucomannan–xanthan gum complex and sodium alginate forms a new, ternary complex.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental fibers were: (1) Positive control: Fructo-oligosaccharide from chicory (Sigma Aldrich Chemie BV, Zwijndrecht, The Netherlands); (2) Negative control: Cellulose (VWR International BV, Roden, The Netherlands); (3) Test fiber: PolyGlycopleX ® (PGX ® ), a soluble high viscosity polysaccharide (HVP) manufactured by a proprietary process (EnviroSimplex ® ) from three dietary fibers; konjac (glucomannan), sodium alginate and xanthan gum (PGX ® : α- d -glucurono-α- d -manno-β- d -manno-β- d -gluco, α- l -gulurono-β- d -mannurono, β- d -gluco-β- d -mannan; InovoBiologic Inc., Calgary, Canada). The carbohydrate properties of PGX have been previously described [ 12 , 13 , 14 ] and show that an interaction between a konjac glucomannan–xanthan gum complex and sodium alginate forms a new, ternary complex.…”
Section: Methodsmentioning
confidence: 99%
“…Harding et al. () reported that the intrinsic viscosity of PGX, which was measured with analytical ultracentrifugation, was higher than the predicted value for the unprocessed mixture of the three NSP. The authors concluded that there is a synergistic interaction among the three NSP in PGX, which is sensitive to the ionic strength of the solvent.…”
Section: Assessmentmentioning
confidence: 94%
“…The applicant claimed that PGX is a ‘novel complex’ rather than a mixture of the three NSP. In this respect, different parameters have been compared between PGX and the three NSP: sedimentation, precipitation, viscosity and macromolecular interactions (Abdelhameed et al., ; Harding et al., , ; Smith et al., ).…”
Section: Assessmentmentioning
confidence: 99%